THE CORRELATION BETWEEN LEPROSY TYPE AND GRADE OF DISABILITY IN LEPROSY PATIENTS IN SAMARINDA - Cristian Bungin; Vera Madonna Lumban Toruan; Yudanti Riastiti (Universitas Muhammadiyah Kalimantan Timur, 2020)
Leprosy or Hansen’s disease is a disease caused by obligate bacteria, Mycobacterium leprae. This disease is a chronic infectious disease with the first affinity in the peripheral nerves. The worst complication of this disease is disability and causes sufferers to be excluded from their social activities. There are several factors that play a role in the occurrence of leprosy defects, one of them is the type of leprosy. This research aims to determine the correlation between the type of leprosy and the grade of disability in leprosy patients in Samarinda. This research was an analytic observational study. Data collection was done by visiting all Community Health Center (Puskesmas) in Samarinda and the medical records of leprosy patients recorded from January 2014-February 2019. The sampling was using a purposive sampling technique. The result showed 106 patients who met the inclusion and exclusion criteria. Data analysis was using the Kolmogrov-Smirnov test which obtained p = 0.764, so it could be concluded that there was no correlation between the type of leprosy and the grade of disability in leprosy patients in Samarinda.